MULTI-DRUG RESISTANT Escherichia coli AND Proteus mirabilis FROM THIRUVANANTHAPURAM, KERALA (INDIA) (Applied Biological Research, 2023)
Escherichia coli and Proteus mirabilis are Gram-negative, rod-shaped uro pathogens that frequently cause urinary tract infections. They have gained  importance due to the emergence of multi-drug resistance in them. This  work compares the antibiotic resistance pattern of clinical isolates of E.  β-lactam resistance mechanism. The antibiotic susceptibility of E. coli and  P. mirabilis was assessed by Kirby-Bauer disc diffusion assay. Extended spectrum β-lactamase was detected by a modified double-disc synergy test  and EZY MICTM strip test. The amplification of drug-resistant gene was  done by PCR. The role of efflux pump was determined by using the efflux  pump inhibitor, carbonyl cyanide 3-chlorophenylhydrazone (CCCP). The  results of antibiotic susceptibility test indicated multi-drug resistant  phenotypes along with tetracycline and β-lactam resistance. E. coli was  found to be extended-spectrum β-lactamase producer; whereas P. mirabilis yielded negative result. PCR results showed the presence of tetA gene in E.  Further, efflux pump assay using efflux inhibitor CCCP proved that the  efflux mechanism causes tetracycline resistance. The study necessitates the  continuous monitoring of antimicrobial drug resistance in uropathogens  for better therapeutic approaches to curtail the risk of AMR.
Keywords: Efflux pumps; extended-spectrum β-lactamase; tetA; Escherichia coli; Proteus mirabilis